The Effect of Polymer Concentration on Oil Recovery - Abdul Aziz, Muhammad Faiz (Universiti Teknologi PETRONAS, 2011)
Enhanced oil recovery consists of three maJor methods which are miscible method, thermal method and chemical method. Polymer flooding is considered as one of the chemical method which is inexpensive compared to other methods. The main objective of this project is to determine the optimum polymer concentration that will bring in the most recovery of oil in Angsi Field. Thus, the (1) polymer concentration, (2) polymer solution viscosity, and (3) polymer injection rate effects towards oil recovery are investigated